Hodnocení finanční situace společnosti a návrhy na její zlepšení - Přikrylová, Andrea (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Předmětem bakalářské práce je zhodnocení finanční situace společnosti KLASIK CZ, s.r.o. za období let 2012 až 2016. Teoretická část se zabývá vymezením pojmů a popisem jednotlivých finančních ukazatelů. V analytické části je provedena samotná finanční analýza a zhodnocení jejích výsledků. V poslední části práce jsou navržena opatření vedoucí ke zlepšení finanční situace společnosti.

The subject of this bachelor thesis is the evaluation of the financial situation of KLASIK CZ, s.r.o. for the period of time 2012 to 2016. The theoretical part deals with the definition of terms and description of financial indicators. In the analytical part is carried out the financial analysis and the evaluation of its results. The last part of the thesis proposes measures which aim to improve the financial situation of the company.
Evaluation of the Financial Situation in the Company and Proposals to its improvement
Keywords: finanční analýza; SWOT analýza; soustavy ukazatelů; likvidita; rentabilita; zadluženost; aktivita; financial analysis; SWOT analysis; systems of indicators; liquidity; profitability; indebtedness; activity